2015
DOI: 10.1016/j.healthplace.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Using cross-classified multilevel models to disentangle school and neighborhood effects: An example focusing on smoking behaviors among adolescents in the United States

Abstract: Background Despite much interest in understanding the influence of contexts on health, most research has focused on one context at a time despite the reality that individuals have simultaneous memberships in multiple settings. Method Using the example of smoking behavior among adolescents in the National Longitudinal Study of Adolescent Health, we applied cross-classified multilevel modeling (CCMM) to examine fixed and random effects for schools and neighborhoods. We compared the CCMM results with those obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 27 publications
6
53
0
Order By: Relevance
“…Therefore, schools may be an important context for reducing the population-level burden of depression by targeting school-level predictors, including school-based interventions. These findings also underscore the need to use CCMM, as these findings would have been missed had we used traditional MLM (34, 52). …”
Section: Discussionmentioning
confidence: 81%
“…Therefore, schools may be an important context for reducing the population-level burden of depression by targeting school-level predictors, including school-based interventions. These findings also underscore the need to use CCMM, as these findings would have been missed had we used traditional MLM (34, 52). …”
Section: Discussionmentioning
confidence: 81%
“…These models assume a two-level structure where adolescents are only nested in neighbourhoods (ignoring schools). Second, a two-level model was run with schools at level-2 (ignoring neighbourhoods) (Dunn et al 2015). Third, in a cross-classified model, individual adolescents were grouped simultaneously into two non-nested contexts (neighbourhood and school).…”
Section: Methodsmentioning
confidence: 99%
“…Results from neighbourhood studies that only assess neighbourhood variation may be misleading if variation from other contexts, such as school, are ignored (De Clercq et al 2014; Dunn et al 2015). Studies that examined adolescent smoking, using cross-classified multilevel models to account for the influence of non-nested contexts (where individuals are nested in schools and neighbourhoods, but schools are not necessarily nested within neighbourhoods or vice versa), found that neighbourhood effects are overestimated when ignoring school-level variation (De Clercq et al 2014; Dunn et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new fruitful area of LCHD epidemiologic research will focus on better characterizing the role and impact of the places where children and families live, grow, learn, work, and play (Pearce 2014;Dunn et al 2015). With the expanding number of place-based interventions that attempt to improve the organization and functioning of entire community ecosystems, there is a mounting interest in how place as an organizing force influences health development at both the individual and population levels.…”
Section: Epidemiological Researchmentioning
confidence: 99%